Evaluation of Physical and Micromorphological Properties of Saprolites for Wastewater Treatment - Chng, Loi Peng (2002)
Saprolite is defined as soft, massive, friable, isovolumetrically weathered bedrock that retains the fabric and structure of the parent rock (Pavich, 1986). It is the transitional material between hard rock and the solum and has characteristics of both the parent rock below and the soil above it (Daniels et al., 1984). Saprolite is currently being used for the on-site treatment and disposal of household wastewater (Vepraskas et al., 1996) and storage of some radioactive wastes (Vepraskas and Williams, 1995). Due to extensive housing development, suitable soils for septic systems are being depleted (Schoeneberger et al., 1995). Thus, a g reater demand is being placed on the use of saprolite for wastewater disposal purposes. The objectives of this study are (1) to study the physical and micromorphological characteristics of different saprolites, (2) to study the saturated hydraulic conductivity of different saprolites, and (3) to correlate the saturated hydraulic conductivity with the physical characteristics and develop models to predict Ksat for different type of saprolites for wastewater treatment. The hydraulic conductivity was carried out in the laboratory using metal core rings (7.62 cm internal diameter x 4 cm long) and double-ring infiltrometer were used in situ. To determine the physical properties, standard method is employed for the particle size distribution, bulk density, particle density, total porosity, penetration resistance, and water retention capability. Micromorphology and scanning electron microscopy were used to observe the microfabrics. The pore size distribution was analyzed using an image analyzer and pore shape was also determined.